145 Survival in lymph node positive vulvar cancer patients treated with adjuvant radiotherapy versus chemoradiotherapy - Santana, Beatriz Navarro; Sanchez, Octavio Arencibia; Laseca-Modrego, Maria; Garcia-Cano, Daniel Gonzalez; Rave-Ramírez, Andrés; Vaswani, Avinash Ramchandani; Martínez, Alicia Martín (International journal of gynecological cancer, 2024)
Introduction/BackgroundVulvar cancer is uncommon accounting for 6330 new cases and 1560 deaths in USA in 2022ESGO guidelines concluded that, sentinel node macrometastasis (>2 mm) are to be treated with inguinal lymphadenectomy followed by radiotherapy in cases with more than one metastatic lymph node and/or extracapsular spread with a II level of evidence and grade A of recommendation- Also, the ESGO guidelines states that adjuvant chemoradiotherapy should be considered with a IV level of evidence and grade B of recommendation.MethodologyRetrospective cohort study which evaluated patients diagnosed with squamous vulvar cancer and positive inguinal lymph nodes. These patients were treated with radiotherapy or with concurrent chemoradiotherapy (cisplatin 40mg/m2 per week) after vulvectomy and inguinal lymphadenectomy. The study took place in Hospital Materno Infantil de Las Palmas, Spain from 1990 to 2022ResultsA total of 27 patients were included, 17 in the group of radiotherapy only and 10 in the group of chemoradiotherapy. There were not differences in terms of age (P=0.27), ECOG status (P=0.091), FIGO 2021 stage(P=0.921), in tumor grade (P=0.449), lymphovascular invasion (P=0.315), the tumor size (P=0.165), the number of lymph node yielded (P=0.56), the number of positive lymph nodes (P=0.147), the surgical margins (P=0.328). In the radiotherapy group there were more radical vulvectomies than in the chemoradiotherapy group (P=0.001).There were not significant differences in overall survival between the radiotherapy alone group vs the chemoradiotherapy group (Log-rank test, P=0.24). In multivariate analysis, only age was a significant prognostic factor for overall survival (HR:1.17, CI95%: 1.05–1.31, P=0.006), however chemoradiotherapy was not significant in univariate (HR:0.52, CI 95%:0.17–1.62, P=0.23) and multivariate analysis (HR:0.09, CI 95%:0.01–1.09, P=0.058).ConclusionIn our study chemoradiotherapy was not an independent prognostic factor for overall survival. We should be cautious interpreting those results because of the small sample of this study and its retrospective nature.DisclosuresNo disclosures.